Household satisfaction and associated factors with community-based health insurance scheme in Ethiopia: systematic review and meta-analysis - Daniel Tarekegn Worede; Mengistie Kassahun Tariku; Melash Belachew Asresie; Belayneh Fentahun Shibesh (BMC, 2023)
Abstract Background Community-based health insurance (CBHI) schemes are crucial for households to avoid financial hardship, improve healthcare quality, and engage in health policies. Household satisfaction is a key indicator for assessing healthcare quality and identifying service gaps. However, research on household satisfaction with CBHI in Ethiopia is limited. Therefore, this study aimed to evaluate household satisfaction and associated factors with CBHI schemes in Ethiopia. Methods A comprehensive search of relevant literature was conducted using multiple databases, including PubMed, Google Scholar, Africa Journal Online, and Ethiopian Universities' institutional open-access online repositories. The search was carried out between January 25, 2023, and February 28, 2023. Twelve primary studies, including eight published and four unpublished, were identified and included in the analysis with a total sample size of 5311 participants. A protocol with the registration number CRD20531345698 is recorded on the Prospero database. Two authors, DT and MK, independently extracted the required data using a standardized form. The extracted data were then analyzed using STATA version 17 software. Heterogeneity was assessed using the Cochrane Q-test and I2 tests. Finally, a random-effect model was employed to calculate the overall household satisfaction with CBHI and to determine the associated factors. Results The meta-analysis showed that the overall household satisfaction with CBHI in Ethiopia was 62.26% (95% CI 53.25-71.21%). The study found regional variations in household satisfaction, with 63.40% in Oromia, 64.01% in Amhara, 49.58% in Addis Ababa, and 66.76% in SNNPs. The study identified several factors associated with household satisfaction and the CBHI scheme, including the availability of drugs (OR 2.13, 95% CI 1.47-2.78), friendly services (OR 3.85, 95% CI 1.60-6.10), affordability of premium (OR 2.80, 95% CI 1.97-3.63), and knowledge/awareness of CBHI (OR 2.52, 95% CI 1.73-3.33). Conclusions The study provides valuable insights into household satisfaction with CBHI in Ethiopia, with a considerable proportion of enrolees being satisfied. The finding highlights regional variations in household satisfaction and underscores the need for tailored interventions and monitoring to enhance CBHI sustainability and effectiveness. The results suggest that healthcare providers and policymakers should prioritize the availability of drugs, friendly services, affordable premiums, and education to improve household satisfaction with CBHI schemes.